Kolaborasi Perawat dan Ahli Gizi dalam Penanganan Masalah Gizi Balita di Wilayah Kerja Puskesmas Halmahera Barat. - Vilia Herani Noky; Kristiani Tauho; Kristiawan Nugroho (Jurnal Epidemiologi Kesehatan Komunitas, 2021)
ABSTRACTBackground: Nutritional status is the body's needs in the growth and development of toddlers. A recent sector study on nutrition development in Indonesia shows that the problem of child nutrition is still quite high in the community. North Maluku Province is the fourth place among the provinces which contributing nutrition problem in 2019 with a percentage of 20.9%. Good nutritional status itself is necessary to the growth and the development of toddlers. Since the number of nutritionists in North Maluku Province is still limited, this study was conducted to explore the collaboration between nutritionists and nurses in handling nutritional problems among toddlers in this province.Methods: This study used a qualitative research method and was conducted in 5 Primary Health Care Centers within the region of West Halmahera District. This research involved 15 participants consisting of nurses, nutritionists and the Heads of Primary Health Care Center. The data collection used in-depth interviews for each participant with a total of research duration of about 2 months.Result: The results showed that the collaboration between nurses and nutritionists was mainly to perform vital body examination and to give supplementary feeding for toddlers. Primary Health Care has a Plan of Action for this program of collaboration. Other than that, sometimes they provide some health education about exclusive breastfeeding, good nutritional intake and the importance of bringing toddlers to the integrated service center called Posyandu.Conclusion : Nurses and nutritionists in West Halmahera collaborate to improve toddlers nutritional status but the collaboration is still limited.